2008
DOI: 10.1902/jop.2008.060522
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking and Alveolar Bone in Young Adults: A Study Using Digitized Radiographs

Abstract: Smoking produces an adverse effect on clinical periodontal variables and alveolar bone height and density, acting as a potential risk factor for alveolar bone loss, even at an early age with low tobacco consumption. It is very important to inform young smokers about the risk of this habit in relation to periodontal health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 75 publications
5
32
0
1
Order By: Relevance
“…The regions of interest (ROIs) were established in 1 mm 2 and were positioned on two regions lateral to the root of the selected site, one placed at the alveolar bone crest (ROI I) and another 3 mm below the first, at the medullar bone (ROI II) ( Fig. 1) (adapted from Rosa et al 2008). To demarcate the ROIs, a standard 1 mm 2 square radiopaque net was placed in the digital sensor, used for calibration together with the radiographic system when evaluating the image.…”
Section: Radiographic Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The regions of interest (ROIs) were established in 1 mm 2 and were positioned on two regions lateral to the root of the selected site, one placed at the alveolar bone crest (ROI I) and another 3 mm below the first, at the medullar bone (ROI II) ( Fig. 1) (adapted from Rosa et al 2008). To demarcate the ROIs, a standard 1 mm 2 square radiopaque net was placed in the digital sensor, used for calibration together with the radiographic system when evaluating the image.…”
Section: Radiographic Measurementsmentioning
confidence: 99%
“…ROI II showed change in the ABD of sites with PPD≥5 mm in δ2. Previus studies (9,20,21) have suggested the use of control ROIs, but the authors did not use the same standard of positioning, also there is still no definition as to which would be the most specific control region. Maybe this region should be located even further from the defect and the treated area, as described by the Hwang et al (9) and Toback et al (21).…”
Section: Periodontal Treatment and Alveolar Bone Densitymentioning
confidence: 99%
“…Recently, digital subtraction radiography has been used to assess the effect of cigarette smoking on alveolar bone (Rosa et al 2008). The selection of areas of interest in the proximal sites allowed determination of CADIA values, which were related to bone density changes.…”
Section: Subtraction Radiography and Periodonticsmentioning
confidence: 99%
“…The prevalence of periodontitis is significantly more pronounced in smokers compared with non-smokers (Do et al 2008;Ojima et al 2006;Rosa et al 2008;Torrungruang et al 2005). Smoking-associated periodontitis typically involves the destruction of the supporting tissues of the teeth, with clinical symptoms of attachment loss, pocket formation, bone loss, and eventually tooth loss (Bergstrom 2004;Ojima et al 2006;Torrungruang et al 2005;Ylostalo et al 2004).…”
Section: Introductionmentioning
confidence: 99%